Discovering Buraydah's Work from Café (WFC) Dynamics in the Post-COVID-19 Landscape - Maspul, Kurniawan Arif (Jurnal Price : Ekonomi dan Akuntasi, 2024)
The global transition to hybrid work patterns following COVID-19 has accelerated the growth of the Work from Café (WFC) phenomena, changing traditional work paradigms and productivity expectations. The study digs into WFC's revolutionary potential, as shown in Buraydah, Saudi Arabia, which is known for its thriving coffee shop scene. Drawing on theoretical frameworks such as environmental psychology, attention restoration theory, Maslow's hierarchy of needs, and social exchange theory, the study investigates WFC's complex dynamics. Overcrowding, noise levels, restricted amenities, and patronage expectations are compared to chances for innovation and collaboration. Infrastructure improvement, community participation, work-life balance promotion, local economic integration, and policy lobbying are among the proposed tactics for long-term WFC practices. These initiatives, based on theoretical foundations and practical facts, seek to maximize WFC's economic and social effect while cultivating thriving, resilient communities in the post-pandemic era.